PERCEPATAN REFORMA AGRARIA UNTUK MENCAPAI KEADILAN - Utomo, Setiyo (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe legal purpose of this study is to analyze the acceleration of agrarian reform implemented by the government so that it has an impact on equitable land management. The impact on land ownership inequality is the occurrence of inequality in land ownership that is not balanced. The acceleration of the agrarian reform program is expected to answer the problem of inequality in assets and access, especially to the object of agrarian reform. This research was conducted through a normative juridical method with a statutory approach and a conceptual approach. The agrarian reform journey through accelerating agrarian reform in structuring assets and compliance with access to produce justice for people who need land for prosperity in life. The state constitution's mandate towards agrarian resources is that the state economy is structured and aimed at the greatest prosperity of the people by developing forms of populist economy. The benchmark for the success of agrarian reform will be the creation of equal distribution of land ownership for prosperity and justice.Keywords: agrarian reform; asset management; justice; provision of accessAbstrakTujuan hukum penelitian ini untuk menganalisa percepatan reforma agraria yang dilaksanakan oleh pemerintah sehingga berdampak terhadap penataan tanah berkeadilan. Dampak terhadap ketimpangan kepemilikan tanah yaitu terjadinya kesenjangan terhadap kepemilikan tanah yang tidak seimbang. Perceaptan program reforma agraria diharapkan mampu menjawab permasalahan atas ketimpangan terhadap asset dan akses terutama pada objek reforma agraria. Penelitian ini dilakukan melalui metode yuridis normatif dengan pendekatan perundang-undangan dan pendekatan konsep. Perjalanan reforma agraria melalui percepatan reforma agraria dalam penataan aset dan penaatan akses sebagai upaya untuk menghasilkan keadilan terhadap masyarakat yang membutuhkan tanah untuk kesejahteraan dalam kehidupan. Amanah konstitusi negara terhadap sumber agraria bahwa perekonomian negara disusun dan ditujukan untuk sebesar-besarnya kemakmuran rakyat dengan mengembangkan bentuk-bentuk ekonomi kerakyatan. Tolak ukur terhadap keberhasilan reforma agraria akan terciptanya pemerataan terhadap kepemilikan tanah untuk kesejahteraan dan keadilan.